Effect of Node Position and Number of Stem Cutting on The Growth and Yield of ‘katuk’ (Sauropus androgynus (L.) Merr.) - Solikin, Solikin (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
Katuk (Sauropus androgynus (L.) Merr.) has potential as a vagetable and medicinal plant. This study aimed to determine effect of node position and number of stem cuttings on the growth of katuk. The experiment used Completely Randomized Design with two treatments arranged in split plots. The node position of stem cuttings as the main plot consists of top stem cutting (T, top – 8 nodes under shoot tip), middle stem cutting (M, 8 – 11 nodes under shoot tip) and bottom stem cutting (B, 16-20 nodes under shoot tip). The node number of stem cuttings as a subplot consists of 2 nodes (J1), 3 nodes (J2), 4 nodes (J3), and 5 nodes (J4). Each treatment combination was replicated three times.The results revealed that the top stem cutting resulted in the highest root, total plant dry weight and leaf area, as well stem cutting with 4 nodes produced the highest total plant dry weight and leaf area.